Pengaruh Kebijakan Pelaporan Pajak dan Sistem DJP Online Terhadap Pelaporan SPT Tahunan Wajib Pajak di KPP Pratama Makassar Barat - Yusria Yusria; Andi Indah Lestari (Journal Axegnal: Tax And Economic Insights Journal, 2025)
ABSTRACT This study aims to analyze the influence of tax reporting policy through DGT Online (e-filling) on the increase in taxpayers' Annual Tax Return reporting at KPP Pratama Makassar Barat. This study uses a quantitative method with a descriptive analysis approach, where data collected through a survey of taxpayers at KPP Pratama Makassar Barat is analyzed using statistical techniques. Along with the development of information technology, the Directorate General of Taxes (DGT) has developed an online-based tax reporting system that is expected to simplify the reporting process and increase taxpayer compliance. The results of the study show that the tax reporting policy through DGT Online, tax reporting is proven to have no effect on increasing taxpayers' annual tax return reporting, but online DGT is proven to have an effect on increasing taxpayers' annual tax return reporting at KPP Pratama Makassar Bar. The study also found that the level of understanding of.